Analisis Docking Molekuler Senyawa Derivat Phthalimide sebagai Inhibitor Non-Nukleosida HIV-1 Reverse Transcriptase - Tiara Ajeng Listyani; Rina Herowati (Jurnal Farmasi Indonesia, 2018)
Phthalimide derivate compounds was reported as a new class of nonnucleoside reverse tranckriptase inhibitors. Docking molekuler analysis in phthalimide derivative compounds against reverse transcriptase enzym necessary to determine the affinity and interaction patterns between the above compounds with reverse transcriptase enzym. Derived compounds phthalimide geometry optimized using VegaZZ software then performed by way of target preparation, ligand preparation, docking method validation, and analysis of docking using PyRx-Python0.8 - AutoDock vina so we get to the target ligand interactions, free energy bonding, hydrogen bonding, and interaction patterns. Interaction pattern seen in thirty-three phthalimide derivatives with reverse transcriptase enzym showed hydrogen bonding with amino acids Lys101 where the interaction is similar to the interaction of TIBO R 86183 compounds which are the original ligands of the target protein.